The McKinsey Framework as an Analysis of Organizational Change Readiness: Public Service Agency State Polytechnic - Rino Desanto Wiwoho; Farida Tri Hastuti; Hendrick Hernando; Hifhzan Frima Thousani (Universitas Muhammadiyah Palu, 2025)
The transformation of state universities operating as work units (PTN-Satker) into state universities with public service agency status (PTN-BLU) is expected to enhance the quality of both academic and non-academic services. Consequently, this transformation will improve the performance of polytechnics, ultimately having a direct impact on students, society, and industry. The McKinsey 7S Framework is used to analyze organizational effectiveness through seven key elements: strategy, structure, systems, style, staff, skills, and shared values. These seven elements within the McKinsey 7S Framework play a crucial role in building strong organizational management. Organizational change is a process in which an organization transitions from its current state to a desired state to enhance its effectiveness. Throughout this transformation process, organizations inevitably face various challenges, obstacles, and constraints. This study utilizes the McKinsey 7S Framework to analyze an organization's readiness for change. This study was conducted by distributing questionnaires both online and offline to respondents comprising academic and administrative staff at PTN-BLU. 57 Respondents' responses were measured using a Likert scale ranging from one to seven. Data analysis was performed using simple linear regression with SPSS version 27 and tabulation with Microsoft Excel. The findings indicate that the McKinsey 7S Framework has a positive and significant influence on organizational change readiness, with a contribution of 71,8%. Furthermore, the results of the simple linear regression analysis produced the equation Y=-4.502+0.170., meaning that every one-unit increase in the McKinsey 7S Framework variable will be followed by a 0.170 increase in organizational change readiness.